2020
DOI: 10.3390/nu12030731
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking and Risk of Breast Cancer: Results from the SUN (‘Seguimiento Universidad de Navarra’) Project

Abstract: Alcohol intake is associated with the risk of breast cancer. Different patterns of alcohol-drinking may have different effects on breast cancer even when keeping constant the total amount of alcohol consumed. We aimed to assess the association between binge drinking and breast cancer risk. The SUN Project is a Spanish dynamic prospective cohort of university graduates initiated in 1999. In the 556-item lifestyle baseline questionnaire a validated food-frequency questionnaire was embedded. Participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Our data also did not allow us to determine the timing of alcohol consumption during the day or week, the quantity consumed per drinking occasion, or whether alcohol was consumed alone or with a meal. 32,37,38 We also relied on self-reported alcohol use, which can be prone to recall bias; however, it has been shown that alcohol levels are highly reproducible using food records and 24-hour recalls. 39,40 Finally, although we adjusted for multiple confounders related to alcohol exposure and the study outcomes, including abstainer bias, residual confounding cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also did not allow us to determine the timing of alcohol consumption during the day or week, the quantity consumed per drinking occasion, or whether alcohol was consumed alone or with a meal. 32,37,38 We also relied on self-reported alcohol use, which can be prone to recall bias; however, it has been shown that alcohol levels are highly reproducible using food records and 24-hour recalls. 39,40 Finally, although we adjusted for multiple confounders related to alcohol exposure and the study outcomes, including abstainer bias, residual confounding cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, most women (84.4%) remained in the same or adjacent category of intake at follow‐up. Our data also did not allow us to determine the timing of alcohol consumption during the day or week, the quantity consumed per drinking occasion, or whether alcohol was consumed alone or with a meal 32,37,38 . We also relied on self‐reported alcohol use, which can be prone to recall bias; however, it has been shown that alcohol levels are highly reproducible using food records and 24‐hour recalls 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Women in the binge drinking group had a higher risk of breast cancer (HR = 1.76; 95% CI 1.03–2.99) than those in the non-binge drinking category. In the stratified analysis, a twofold higher risk for premenopausal breast cancer was associated with a binge drinking habit (HR = 2.06; 95% CI 1.11–3.82) [ 42 ].…”
Section: Alcohol Effects On Breast Cancermentioning
confidence: 99%
“…The Mediterranean Diet Score proposed by Trichopoulou et al [26] was used to evaluate the adherence to the Mediterranean dietary pattern, excluding alcohol intake. We considered alcohol consumption as a separate covariate given the growing evidence on its association with several ORC [27,28]. The questionnaire also gathered information on the participants' average time of sunlight exposure.…”
Section: Covariate Assessmentmentioning
confidence: 99%